Change in trunk muscle activity during incline treadmill running - Ewbank, P. T.; Jensen, R. L. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
This study examined the effect that increasing incline has on the muscle activity of three different muscles of the trunk during treadmill running. Eight female subjects participated in 3 consecutive 30 second trials, running at a pace equal to their personal best for a cross country race. The three trials were completed at inclines of 0, 2 and 4 percent. Surface electromyography data was recorded on the rectus abdominis, external oblique and multifidus. All muscle activity was recorded on the left side of the subjects. Results showed that there is no significant interaction between muscle activity and change inincline. The results did show that there is a significant difference in muscle activity between the different muscles during all four phases of the running stride.